PERANAN KERAPATAN ADAT NAGARI (KAN) DALAM PENYELESAIAN SENGKETA TANAH KAUM DI NAGARI KOTO ANAU KABUPATEN SOLOK PROPINSI SUMATERA BARAT - , SUDIANTO MANULLANG, Dr. Danardono, M.PH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Factor of interest rate and mortality is former principal components to get premium of term insurance. Vasicek's rate of interest model is one of stochastic rate of interest model that is utilized on derivatif that becomes discount factor of zero coupon bond's price, and solved by Affine's model to get annuity, actuarial value so results annual net premium of term insurance.